2009
DOI: 10.1007/s10570-009-9378-x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated total reflectance Fourier-transform Infrared spectroscopy analysis of crystallinity changes in lyocell following continuous treatment with sodium hydroxide

Abstract: Cellulose is a linear 1,4-b-glucan polymer where the units are able to form highly ordered structures, as a result of extensive interaction through intra-and intermolecular hydrogen bonding of the three hydroxyl groups in each cellulose unit. Alkali has a substantial influence on morphological, molecular and supramolecular properties of cellulose II polymer fibres causing changes in crystallinity. These physical changes were observed herein using ATR-FTIR spectroscopy, following continuous treatment of the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(90 citation statements)
references
References 36 publications
5
83
0
2
Order By: Relevance
“…The broad band between 3600-3000 cm -1 was assigned to hydrogen bonds between OH groups of cellulose II structure, where the 3488 cm -1 and 3447 cm -1 absorptions were due to the general OH stretching and specific O(3) H….O(5) vibration due to the intramolecular hydrogen bonds in the cellulose II unit cell, respectively. Similar FTIR peaks for the cellulose II has previously been reported (Carrillo, Colom, Sunol & Saurina, 2004;Široký, Blackburn, Bechtold, Taylor & White, 2010), however the previous studies reported the O(3)H-O(5) vibration at 3442cm -1 .…”
Section: Atr-ftir and Waxd Analyses Of Fibre Supramolecular Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…The broad band between 3600-3000 cm -1 was assigned to hydrogen bonds between OH groups of cellulose II structure, where the 3488 cm -1 and 3447 cm -1 absorptions were due to the general OH stretching and specific O(3) H….O(5) vibration due to the intramolecular hydrogen bonds in the cellulose II unit cell, respectively. Similar FTIR peaks for the cellulose II has previously been reported (Carrillo, Colom, Sunol & Saurina, 2004;Široký, Blackburn, Bechtold, Taylor & White, 2010), however the previous studies reported the O(3)H-O(5) vibration at 3442cm -1 .…”
Section: Atr-ftir and Waxd Analyses Of Fibre Supramolecular Propertiessupporting
confidence: 86%
“…Nelson and others (Nelson & O'Connor, 1964a, b) proposed the band at 2900 cm -1 was due to the C-H stretching in Cellulose I and Cellulose II structures and they used the intensity ratio of the 1372 cm -1 and the 2900 cm -1 bands as a measure of the total crystallinity index for cellulose fibres. In this study intense bands of the same magnitude were observed at 2892 cm -1 for both Lyocell and the ReCell fibres and similar absorption intensities were reported for other lyocell fibrous materials (Široký, Blackburn, Bechtold, Taylor & White, 2010). Examination of the ATR-FTIR spectra of the Lyocell and ReCell fibres in the 2000cm -1 -800cm -1 region indicated that the fibres have similar structural features, Figure 2.…”
Section: Atr-ftir and Waxd Analyses Of Fibre Supramolecular Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…In previous research we have demonstrated that ATR-FTIR can be successfully employed to monitor changes in crystallinity of cellulosic fibres through crystallinity indices [55,56].…”
Section: Attenuated Total Reflectance Fourier-transform Infrared (Atrmentioning
confidence: 99%
“…FourierTransform Infrared spectroscopy (FT-IR) is currently one of the best available techniques in the textile science to obtain structural information (Široká et al, 2011), which has been universal accepted for many years as a powerful tool for analytical and chemical characterisation in wide range of scientific disciplines and widely used in polymer characterisation, providing information about chemical nature, isomerisation, conformational order, state of order, and orientation. Using FT-IR, a clear relationship between interaction of hydroxyl groups and crystallinity in cellulose has been established, and numerous papers have been published in relation to infrared spectroscopy analysis of native cotton and mercerised cotton as well as regenerated fibres (Hurtubise & Krassig, 1960;Nelson & O'Connor, 1964;Široký et al, 2010) in order to establish or develop the ratio indices of absorption bands, crystallinity indices, the so-called 'total crystallinity index' (TCI) and 'lateral order index' (LOI). TCI represents the overall degree of order in cellulose given by the ratio of absorption at 1372 cm -1 (C-H deformation in cellulose II) and 2892 cm -1 (C-H stretch in cellulose II).…”
Section: Attenuated Total Reflectance Fourier-transform Infrared Specmentioning
confidence: 99%